VRIO 분석을 통한 대한민국과 일본 축구 국가대표팀의 경쟁 우위 비교 연구 - 김진국; Jin Kook Kim (Ch'eyuk kwahak yŏn'gu, 2025)
[목적] 본 연구는 VRIO(Value, Rarity, Imitability, Organization) 모델을 활용하여 일본 축구 국가대표팀과 한국 축구 국가대표팀의 경쟁 우위를 분석하고, 이를 바탕으로 한국 축구의 발전 전략을 제시하는 것이 그 목적이다. [방법] 이를 위해 문헌연구와 사례연구, 그리고 축구 전문가를 대상으로 한 반구조화된 인터뷰를 병행하였다. 주요 결과는 다음과 같다. [결과] 일본 축구는 체계적인 유소년 육성 시스템, 데이터 기반 전략, 클럽과 대표팀 간의 조직적 연계를 통해 VRIO의 모든 요소를 충족시키며 국제 대회에서 안정적인 성과를 내고 있다. 반면, 한국 축구는 뛰어난 개인 선수 자원을 보유하고 있으나, 유소년 시스템의 지역적 불균형과 데이터 활용의 미흡, 클럽과 국가대표팀 간 협력 부족으로 인해 VRIO 요소를 충분히 충족시키지 못하고 있다. [결론] 한국 축구의 발전을 위해서는 장기적 마스터 플랜 구축, 유소년 시스템의 강화, 데이터 기반 접근법의 도입, 클럽과 국가대표팀 간의 협력 구조 개선이 필요하다는 결론에 도달하였다. 본 연구는 VRIO 모델을 활용한 국가대표 축구팀의 전략적 경쟁력 분석 사례로서, 한국 축구가 장기적이고 지속 가능한 발전을 이룩하기 위한 구체적인 방향성을 제공한다. PURPOSE This study aims to analyze the competitive advantages of Japanese and South Korean national football teams using the value, rarity, imitability, and organization (VRIO) model. Based on the results, it proposes strategies for the development of South Korean football. METHODS The research methodology is a combination of literature review, case study, and semi-structured interviews with football experts. RESULTS The Japanese football system meets all criteria of the VRIO model through its systematic youth development system, data-driven strategies, and organizational linkage between clubs and the national team, which has led to consistent performance in international tournaments. In contrast, while South Korean football possesses excellent individual player resources, it fails to fully meet the criteria of the VRIO due to a regional imbalance in the youth system, insufficient use of data, and lack of cooperation between clubs and the national team. CONCLUSIONS The interview data indicate that strengthening the youth system, adopting a data-driven approach, and improving the collaborative structure between clubs and the national team are necessary components of the development of South Korean football. This study provides specific directions for the long-term and sustainable development of South Korean football by analyzing the strategic competitiveness of national football teams in other countries using the VRIO model.